Pediatric Deaths and Venipuncture - Chung, Taek; Park, Sohyung; Kim, Hye-Jeong; Yang, Kyoungmoo; Ha, Hongil (Korean Journal of Legal Medicine, 2018)
Venipuncture is a routine and relatively safe and painless medical procedure, necessary for accurate diagnosis and treatment. However, given that pain related to medical procedures may have adverse effects for children, could venipuncture cause deaths in infants and children? We analyzed our cases of unexpected death after venipuncture and conducted a literature review on them. A vasovagal response to noxious stimuli may explain such a sudden death immediately after venipuncture, commonly presented as needle phobia, breathholding spell, and reflex anoxic seizure in the literature, despite the fact that the current medical evidence is not enough to prove their casual relationship. In addition, pain prevention and management during medical procedure is incorporated in clinical guidelines for pediatric patients, because painful medical procedures negatively affect child development. Thus, prevention and management of pain related to medical procedure may be helpful to avoid an adverse vasovagal response to noxious stimuli from occurring. KCI Citation Count: 0